Technology adoption in Cambodia under a participatory development approach - Chap, Nimol; Tolentino, Lutgarda L. (2007)
The paper argues that the adoption of agricultural technology is influenced not only by the use of the participatory approach, but by farmers' access to resources such as water, capital and labor and the technology's characteristics, for example, ease of application. These were the findings of a study conducted in 2004 in Ampoeu Prey and Kandaok communes in Cambodia where New Humanity implemented its Mixed Farming Development Project.
Keywords: Technology adoption patterns